Advancements in fragility analysis using numerical calibration methods for a horizontally curved RC bridge. (15th October 2016) - Movaghati, Sepehr; Abdelnaby, Adel E.
Highlights: Develop a calibrated model for a curved bridge. Select a suite of ground motion records with wide variation parameters. Derive fragility relationships using calibrated model and un-calibrated models. Compare fragility relationships for the bridge using both models. Highlight the significance of forces interaction on fragility relationships. Abstract: Horizontally curved reinforced concrete (RC) bridge piers are subjected to combined actions of axial, shear, bending and torsion. The interaction between these combined forces in the highly inelastic range significantly influences the response of the bridge piers. In this paper, a three-dimensional fiber-based finite element model of a curved bridge is developed. The model is then calibrated based on experimental data. The calibration process is conducted with the objective of developing a computationally inexpensive model that can accurately mimic the response of bridge piers subjected to complex multi-directional earthquake loading conditions. An evaluation of the seismic fragility relationships of a curved bridge is undertaken using the initial (un-calibrated) and calibrated numerical models. The results from both models indicate that combined forces interaction significantly affect fragility relationships.